A Study on Impact of Globalization and Small Scale Industry: Present Scenario (International Journal of Food and Nutritional Sciences, 2022)
Globalization has hit small manufacturers as they cannot compete with MNCs or largemanufacturers or manufacturers. Many workers have become jobless due to closure of many units. InIndia, the above description makes it clear that the impact of globalization has not been uniform.Globalization has led to uneven competition between giant MNC's and dwarf Indian industries. Thesmall scale industry sector is an important component of the overall industrial sector of the country.Increased competition from foreign companies can put pressure on local companies, making it harderfor them to succeed.